Positive and negative affect are associated with salivary cortisol in the everyday life of older adults: a quantitative synthesis of four aging studies - Pauly, Theresa; Drewelies, Johanna; Kolodziejczak, Karolina; Katzorreck, Martin; Lücke, Anna J.; Schilling, Oliver; Kunzmann, Ute; Wahl, Hans-Werner; Ditzen, Beate; Ram, Nilam; Gerstorf, Denis; Hoppmann, Christiane A. (Psychoneuroendocrinology, 2021)
Research on time-fluctuating links between positive affect and cortisol is inconsistent and mostly based on young to middle-aged samples. The current project investigated how moment-to-moment changes in positive and negative affect are associated with moment-to-moment changes in cortisol levels in older adults’ daily lives and whether those associations are moderated by differences in health status (as indicated by the number of comorbidities). Affect and cortisol data collected in four separately conducted momentary assessment studies with parallel protocols were pooled to obtain a sample of N=476 individuals aged 56-88 years (Mage=71.9, SD=6.6; 52% female). Participants provided affect reports and collected salivary cortisol 5-7 times a day for a 7-day period and reported the presence of 13 different health conditions. Data were analyzed using multilevel models, with time since waking, daily behaviors associated with cortisol secretion, age, and sex controlled. Feeling more positive affect than usual was associated with lower momentary cortisol. In contrast, feeling more negative affect than usual was associated with higher momentary cortisol. Associations of momentary positive and negative affect with cortisol were weaker among participants in worse as compared to those in better health. Trait positive affectivity was associated with more curvature of waking cortisol profiles and trait negative affectivity was associated with smaller cortisol awakening responses. Findings suggest that HPA axis responses fluctuate with everyday changes in positive and negative affect in older adults, and that higher HPA reactivity may indicate preserved health in this age group.